An overview of the toxic effect of potential human carcinogen Microcystin-LR on testis - Lone, Yaqoob (Toxicol Rep, 2015)
The worldwide occurrence of cyanobacterial blooms due to water eutrophication evokes extreme concerns. These blooms produce cyanotoxins which are hazardous to living organisms. So far among these toxins, Microcystin-LR (MC-LR) is the most toxic and the most frequently encountered toxin produced by the cyanobacteria in the contaminated aquatic environment. Microcystin-LR is a potential carcinogen for animals and humans, and the International Agency for Research on Cancer has classified Microcystin-LR as a possible human carcinogen. After liver, testis has been considered as one of the most important target organs of Microcystin-LR toxicity. Microcystin-LR crosses the blood–testis barrier and interferes with DNA damage repair pathway and also increases expression of the proto-oncogenes, genes involved in the response to DNA damage, cell cycle arrest, and apoptosis in testis. Toxicity of MC-LR disrupts the motility and morphology of sperm and also affects the hormone levels of male reproductive system. MC-LR treated mice exhibit oxidative stress in testis through the alteration of antioxidant enzyme activity and also affect the histopathology of male reproductive system. In the present review, an attempt has been made to comprehensively address the impact of MC-LR toxicity on testis.